1995
DOI: 10.1128/mcb.15.2.1071
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Growth of a Murine Lymphoma Cell Line Alters Regulation of Expression of HSP72

Abstract: We have identified a murine B-cell lymphoma cell line, CH1, that has a much-diminished capacity to express increased levels of heat shock proteins in response to heat stress in vitro. In particular, these cells cannot synthesize the inducible 72-kDa heat shock protein (HSP72) which is normally expressed at high levels in stressed cells. We show here that CH1 fails to transcribe HSP72 mRNA after heat shock, even though the heat shock transcription factor, HSF, is activated correctly. After heat shock, HSF from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…13). More recently, the same deficiency was found in a glucocorticoid-resistant rat hepatoma clone (14) and in the murine lymphoma line CH1, where, interestingly, hsp70 heat shock responsiveness was restored when the cells were grown as a tumor and heated in situ (15). Based on results of gel shift analyses and/or transfection studies, a trans-acting defect, possibly in HSF, was proposed as the cause for the lack of hsp70 responsiveness in the MEL, MPC-11, PCC4, and PCC7 mouse lines (11)(12)(13).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…13). More recently, the same deficiency was found in a glucocorticoid-resistant rat hepatoma clone (14) and in the murine lymphoma line CH1, where, interestingly, hsp70 heat shock responsiveness was restored when the cells were grown as a tumor and heated in situ (15). Based on results of gel shift analyses and/or transfection studies, a trans-acting defect, possibly in HSF, was proposed as the cause for the lack of hsp70 responsiveness in the MEL, MPC-11, PCC4, and PCC7 mouse lines (11)(12)(13).…”
mentioning
confidence: 62%
“…Based on results of gel shift analyses and/or transfection studies, a trans-acting defect, possibly in HSF, was proposed as the cause for the lack of hsp70 responsiveness in the MEL, MPC-11, PCC4, and PCC7 mouse lines (11)(12)(13). In the case of the rat hepatoma clone, a defect specific to the hsp70 gene itself was one of the possibilities considered (14), and, in the case of CH1 cells, a requirement for additional regulatory factors to activate hsp70 expression was suggested (15). None of the previous studies has identified the exact nature of the defect, however.…”
mentioning
confidence: 99%
“…Because Hsp70 confers cell protection against different stresses, it has been hy-pothesized that this protein plays a protective role in tumor growth in vivo (Barnes et al 2001;Ravagnan et al 2001). Indeed, CH1 lymphoma cells in culture methylate and silence their Hsp70 promoter, but upon injection into a mouse Hsp70 production in the CH1 cells is restored (Davidson et al 1995). These data suggest that Hsp70 is needed for in vivo tumor progression.…”
Section: Introductionmentioning
confidence: 75%
“…Sham preconditioned animals subjected only to general anesthesia and a paramedian sternotomy were not protected against infarction. Moreover, sham IP had no effect on HSP70.1 and HSP70.3 mRNA or protein expression but did increase HSF activation in the nucleus compared with negative controls (unpublished observation), an event that has been shown to be insufficient to result in HSP70 translation (5). These data suggest that in an open-chest mouse model, sham operation may induce a minor stress that initiates cell signaling pathways but is insufficient to induce de novo HSP70.1 or HSP70.3 transcription or translation.…”
Section: Discussionmentioning
confidence: 99%